Are there differences between comparison methods used to evaluate the accuracy and reliability of digital models? - Leonardo Tavares Camardella; Hero Breuning; Oswaldo de Vasconcellos Vilella
ABSTRACT Objectives: The accuracy and reliability of plaster models and digital models acquired with two different surface laser scanners were tested by means of three methods: measurement with calipers, digital measurement with proper software and superimposition of the digital models. Methods: Thirty plaster models with permanent dentition that met the inclusion criteria were selected and scanned with two laser scanners (R700 and Xcad). Three examiners measured distances on plaster models with a digital caliper and on digital models using Ortho Analyzer software. The digital models were also compared by means of superimposition of the models using the Geomagic Qualify software. The intra and inter-examiner reliability of the measurements were evaluated using the ICC. Paired t test was used to test the accuracy of the measurements on digital and plaster models. Results: The measurements on plaster and digital models acquired by two different scanners showed high values for the ICC. Although statistically significant differences between the measurements on plaster and digital models have been found, these discrepancies were not considered clinically relevant. The superimposition method with Geomagic Qualify software showed that the two digital models were not significantly different. Conclusions: Digital models created from scanned plaster models using the R700 or Xcad scanners were clinically accurate according to the two methods of comparison used.